Anti-Aging Efficacy of Averrhoa bilimbi Fruit Extract Cream: A Human Clinical Trial - Suharsanti, Ririn; Ryan Radix Rahadhian, Muhammad; Sugihartini, Nining; Lukitaningsih, Endang (Tropical Biopharmaca Research Center, IPB University, 2025)
Averrhoa bilimbi, a plant native to Indonesian, exhibits antioxidant, sunscreen, and tyrosinase inhibitory activities due to its polyphenol and flavonoid content. This study aimed to evaluate the anti-aging efficacy of a topical cream containing A. bilimbi fruit extract through a human clinical trial. The extract was obtained by maceration using 70% ethanol and formulated into a water-in-oil (W/O) cream at concentrations of 1% (F1), 3% (F2), and 5% (F3). Each formulation was evaluated for its physical characteristics, including organoleptic properties, homogeneity, pH, and viscosity. Irritation tests were conducted on animals and human volunteers. A total of 24 human subjects applied the cream for 30 days. Skin condition parameters—sebum, moisture, pigmentation, pore size, elasticity, and collagen fibers—were assessed before and after treatment using a skin analyzer. The results showed that the F3 formulation produced the most notable improvements, including increased skin moisture and elasticity, and decreased pigmentation and pore size. Statistical analysis revealed significant improvements (p < 0.05) in pore size and elasticity for the F3 group. These findings indicate that the 5% A. bilimbi extract cream is a safe and effective anti-aging topical formulation.